The elephant in the room: Introduced species also profit from refuge creation by artificial fish habitats. (March 2023) - Gauff, Robin P.M.; Joubert, Etienne; Curd, Amelia; Carlier, Antoine; Chavanon, Fabienne; Ravel, Christophe; Bouchoucha, Marc
Abstract: Increasingly, ecological rehabilitation is envisioned to mitigate and revert impacts of ocean sprawl on coastal marine biodiversity. While in the past studies have demonstrated the positive effects of artificial fish habitats in port areas on fish abundance and diversity, benthic colonization of these structures has not yet been taken into consideration. This could be problematic as they may provide suitable habitat for Non-Indigenous Species (NIS) and hence facilitate their spreading. The present study aimed to examine communities developing on artificial fish habitats and to observe if the number of NIS was higher than in surrounding equivalent habitats. The structures were colonized by communities that were significantly different compared to those surrounding the control habitat, and they were home to a greater number of NIS. As NIS can cause severe ecological and economical damages, our results imply that in conjunction with the ecosystem services provided by artificial fish habitats, an ecosystem disservice in the form of facilitated NIS colonization may be present. These effects have not been shown before and need to be considered to effectively decide in which situations artificial structures may be used for fish rehabilitation. Graphical abstract: Image 1 Highlights: Eco-engineered artificial nurseries are increasingly used for fish restoration. Benthic colonization of these structures has however not yet been investigated. Communities on eco-engineered substrates differ from those of others in the marina. A higher number of introduced species was found on eco-engineered structures. The risk linked to introduced species must be considered when restoring urban habitats.